Design, synthesis and spectroscopic characterisation of a focused library based on the polyandrocarpamine natural product scaffold. (23rd April 2013) - Baron, Paul S.; Neve, Juliette E.; Camp, David; Suraweera, Lekha; Lam, Ann; Lai, John; Jovanovic, Lidija; Nelson, Colleen; Davis, Rohan A.
<x xml:space="preserve">Abstract</x> A focused library based on the marine natural products polyandrocarpamines A (1) and B (2) has been designed and synthesised using parallel solution‐phase chemistry. In silico physicochemical property calculations were performed on synthetic candidates in order to optimise the library for drug discovery and chemical biology. A library of ten 2‐aminoimidazolone products (3–12) was prepared by coupling glycocyamidine and a variety of aldehydes using a one‐step stereoselective aldol condensation reaction under microwave conditions. All analogues were characterised by NMR, UV, IR and MS. The library was evaluated for cytotoxicity towards the prostate cancer cell lines, LNCaP, PC‐3 and 22Rv1. Copyright © 2013 John Wiley & Sons, Ltd.